Technology-Based Self-Directed Learning Model Adaptability for Physical Education in High School (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The purpose of the study is to investigate the main factors of self-directed learning in online digital environments, combining them into a model for physical education (PE) and educational policy formation. According to WHO, physical education tends to decline from an early age. However, experiences in early childhood shape pupil’s engagement in physical activity (PA), smoothing their learning in the future, without sacrificing their natural ability to play in varied environments. The Lithuanian General Framework for Physical Education mentions that physical and health education is considered as a (pre)subject area of the curricula applied in educational institutions, which also introduces the use of digital technologies to develop PA. It is important that the model of technology-based self-directed learning helps to create the necessary environment for the learner and takes into account the most critical PE factors necessary for self-directed learning. Implementation of self-directed learning differs fundamentally at various levels of PE, such as elementary, high school, or higher education levels.Methods: A qualitative study of empirical data collection, qualitative content analysis, qualitative (semi-structured interview) and quantitative research (sociological survey) will be carried out.Results: This project offers innovative research, as self-directed learning is a new and promising educational paradigm. It is also complex due to the nature of the research object, crucial to identify challenges in the real-time application of technology in self-directed learning to enhance learners’ abilities and independence. Additionally, it is expected to foster dialogue between learners, PE teachers, and technology developers in order to address didactic learning issues. A technology-enhanced self-directed learning model will be developed to support PE in policy-making. It will help create an optimal environment for pupils in grades 9–12 while considering key PE factors essential for self-directed learning.Conclusion: The project will have a positive impact on the approach to technology-based self-directed learning, raising physical education level and will bring significant changes to the professional growth of the project participants themselves.Support/Funding Source: This research is co-funded by the European Union (the project “Breakthrough in Educational Research” No 10-044-P-0001) under the 1st April 2025 Agreement with the Research Council of Lithuania (RCOL)).